Randomized clinical trial of autologous skin cell suspension combined with skin grafting for chronic wounds. Issue 2 (27th January 2015) - Hu, Z -C; Chen, D; Guo, D; Liang, Y -Y; Zhang, J; Zhu, J -Y; Tang, B
Abstract: Background: Treatment of chronic wounds using traditional surgical procedures is challenging because of the low graft take rates. This study investigated the combination approach of split-thickness autografts with harvested skin cell suspension for chronic wound treatment. Methods: This randomized clinical trial enrolled patients with chronic wounds between March 2012 and December 2013. Patients who were assigned randomly to the active treatment received a split-thickness autograft combined with harvested skin cell suspension. Control patients received the split-thickness autograft alone. The primary outcome was the rate of complete wound closure by postoperative day 28. Analysis was by intention to treat. Patients who achieved wound closure were followed up for a minimum of 6 months to evaluate the quality of healing. Results: A total of 88 patients were included, 44 in each group. More patients achieved complete wound closure in the skin cell group than in the control group (41 versus 34 patients; P = 0·035). Complete wound closure was observed at a median of 14 (95 per cent c.i. 12·0 to 16·0) days in the skin cell group and 20 (15·7 to 24·3) days in the control group ( P = 0·001). The skin cell group had significantly fewer complications (4 versus 11 patients; P = 0·047). The autografted sites displayed better physical attributes and a reduced tendency for wound recurrence in the skin cell group. Conclusion: Complementary split-thickness autologous skin grafting with autologous skin cells harvested using ReCell® (Avita Medical, Cambridge, UK) technology improved the healing rate of chronic wounds. Registration number: UMIN000011966 (http://www.umin.ac.jp/ctr ). Abstract : Adjunct to skin grafting